Caracterização de uma argila caulinítica de Vitória da Conquista Bahia - Oliveira, Orley Magalhães de (2011)
The kaolinitic clays are widely used in ceramic industry. Those with a light coloring after firing are of interest for the production of coatings due to their aesthetic. Clays from the Southwest Vitoria da Conquista, Bahia, were characterized in order to check their properties and composition. The used methods were Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis, water absorption, shrinkage by firing, flexural tensile by strength and x rays powder diffraction. The samples were fired at 1100 oC and 1200 oC. The analyses show that it is clay containing mainly kaolinite, quartz and mica. A particle size analysis showed that only 35% of the sample passes through the 200 sieve (0.075 mm). The percentages found in the atomic absorption test indicate that the samples are composed mainly of SiO2 and Al2O3, compounds that were confirmed by the Rietveld method. After firing, these clays had a light color, which is recommended for the manufacture of ceramic products and traditional handicrafts.